Study of transport properties in graphene nanostructures in the presence of deformations - Torres Montilla, Vanessa Carolina (2017)
We study the effect of the out-of-plane deformations on the electronic and transport properties of particular graphene nanostructures. Specifically, we consider graphene nanoribbon, hexagonal and triangular graphene flakes, with armchair and zigzag edges. For this purpose, we considered a first neighbour tight-binding approach and the linear elasticity theory. The conductance and electronic density of state were carried out by using the Landauer-Büttiker formalism and recursive Green’s function method for a multiterminal system. For armchair graphene nanoribbons with fold-like deformation, as the translation symmetry is preserved, the conductance is still marked by a sequence of plateaux, similar to the case of pristine graphene nanoribbons. Here, we found that the energy gap can be drastically modulated by changing the deformation parameters, and that relative length of the deformed structure plays a key role in determining the energy gap and its maximum values. In addition, we show that the numerical results are analytically predicted by solving the Dirac equation for the strained system. Graphene flake systems were studied taking into account three types of mechanical out-of-plane deformations: Gaussian-like, fold-like and smoothing fold. For undeformed systems, the electronic properties are influenced by edges, shape and size. In fact, the triangular zigzag graphene flakes exhibit edge states at the Fermi energy, while localized states in the corners are observed in the case of triangular armchair flakes. On the other hand, the conductance for three-terminal undeformed triangular flake presents a similar behavior to the ballistic transport, while hexagonal flake systems are characterized by resonant states and extended bands for zigzag and armchair case, respectively. For deformed graphene flake systems, resonant levels are more impressive for hexagonal than triangular at lower energies. In triangular flakes, the electronic transport is more sensible to deformations extended to the leads. Finally, we study the effects of the sublattice asymmetry originated by a Gaussian-like deformation in the graphene sheet and graphene nanoribbons, on the adsorption of one hydrogen-like atom. It was shown that in graphene sheet one sublattice can be more energetically favorable for impurity adsorption than the other and that this feature can be controlled by varying the strain parameters, while in a graphene nanoribbons, absortion of impurities at the edges are more favourable, despite of the deformation.